The effectiveness of fermented restaurant wastes addition on peat water that is used as Spirullina sp. culturemedia - Patriodi, Rio; Budijono, Budijono; Harahap, Sampe (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTWaste pollution One of the distributors that produces liquid waste and has the potential to pollute water is restaurants.Peat water has a low nutrient content, but can be enriched by addition of fermented restaurant waste. This media can be used to grow Spirullina sp. This study aims to determine the effect of the addition of fermented restaurant waste as an alternative nutrient for the growth of Spirullina sp. This research was conducted in September-October 2019. RAL method was applied with 5 concentrations of fermented restaurant waste solutions, there were 400 ml / 2 L (P1), 800 ml / 2 L (P2), 1,200 ml / 2 L (P3), 1,600 ml / 2 L (P4), 0 ml / 2 L (P0/ control), with 3 repetitions. Each experimental unit was added with 100 ml of Spirullina sp (106 cells/L) and cultured for 10 days. Results shown that Spirullina sp. grow well in all treatments, except control. The best results were obtained in P3 (5,625 x 106 cells/L and 3.0 g/L dried biomass) thatwas achieved in the 8th day. Based on the data obtained, it can be concluded that peat water can be enriched by fermented restaurant waste and can be used as nutrition for the growth of Spirullina sp.Keywords :Pollution, Organik Matters, Microalgae, Alternative Nutrient.